Analisis Kandungan Rhodamin B Pada saus Tomat Yang Beredar DiKabupaten Wajo Kecamatan Belawa Menggunakan Metode Spektrofotometri UV-Vis - Hudayanti, Andi Isti; Widiastuti, Harti; Suhaenah, Asriani (PHARMACY UMI JOURNAL SYSTEM, 2023)
Rhodamin B is a synthetic dye that is used as a dye for the textile industry which is dangerous. Rhodamin B is often misused as a food and cosmetic coloring agent, where Rhodamin B can cause irritation to the digestive tract, poisoning and can even cause cancer. This study aims to determine the presence or absence of Rhodamin B content in tomato sauce samples circulating in Wajo District, Belawa District. In this study used six samples marked with S1, S2, S3, S4, S5, and S6. Qualitative analysis used the TLC test and quantitatively for positive samples used the Uv-Vis spectrophotometry method. From the research results, it was found that S1, S2, S3, S4, S5 were negative for Rhodamin B while S6 was positive for Rhodamin B where the Rf value was 0.68, the color of the pink stain matched the Rhodamin B comparison.